2017
DOI: 10.1007/s00404-017-4340-x
|View full text |Cite
|
Sign up to set email alerts
|

Total bilateral salpingectomy versus partial bilateral salpingectomy for permanent sterilization during cesarean delivery

Abstract: Rates of short-term complications are similar in patients undergoing bilateral partial salpingectomy and total salpingectomy during cesarean deliveries, making the latter a feasible alternative to the former.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 19 publications
2
24
0
2
Order By: Relevance
“…Cesarean section is the most frequent operation performed in women worldwide and now in Egypt is considered to be an epidemic procedures, so this could be an opportunity to introduce the concept of bilateral total salpingectomies (BTS) as an effective sterilization procedure as well as ovarian cancer (OvCa) risk-reducing as a primary prevention in average-risk women for OvCa, in parturients undergoing CS and requiring permanent sterilization. Bilateral partial salpingectomies (BPS) is the commonest performed surgical sterilization at CS as it is easy, safe as well as highly feasible [18,19,20] . BPS is found to be the most effective tubal sterilization with low ectopic rate [13,14] as well as might reduce the ovarian cancer risk especially type I endometrioid and clear cell carcinoma between 42% and 78% [10,11,12] , however recent literatures introduce BTS as more effective superior procedure than BPS regarding contraceptive efficacy, eliminating risk of hydrosalpinges, pyosalpinges, adnexal accident, ectopics as well as effectively reducing OvCa especially type II high grade serous ovarian carcinomas (HGSOCs) as reviewed by Dilley et al [6] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cesarean section is the most frequent operation performed in women worldwide and now in Egypt is considered to be an epidemic procedures, so this could be an opportunity to introduce the concept of bilateral total salpingectomies (BTS) as an effective sterilization procedure as well as ovarian cancer (OvCa) risk-reducing as a primary prevention in average-risk women for OvCa, in parturients undergoing CS and requiring permanent sterilization. Bilateral partial salpingectomies (BPS) is the commonest performed surgical sterilization at CS as it is easy, safe as well as highly feasible [18,19,20] . BPS is found to be the most effective tubal sterilization with low ectopic rate [13,14] as well as might reduce the ovarian cancer risk especially type I endometrioid and clear cell carcinoma between 42% and 78% [10,11,12] , however recent literatures introduce BTS as more effective superior procedure than BPS regarding contraceptive efficacy, eliminating risk of hydrosalpinges, pyosalpinges, adnexal accident, ectopics as well as effectively reducing OvCa especially type II high grade serous ovarian carcinomas (HGSOCs) as reviewed by Dilley et al [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, this study demonstrated that both procedures were equally feasible as well as perioperative surgical consequences were similar (P > 0.05). Studies were evaluating BTS versus BPS at the time of CS concentrating on feasibility as well as perioperative surgical consequences [16,17,18,19,20,21,22] , while there is only one published RCT assessed procedures impacts on ovarian reserve (23). Researchers report a variable degree of feasibility, perioperative surgical consequences and this could be explained based on heterogeneity in surgical experiences as well as surgical techniques and surgical instruments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female tubal occlusive permanent contraception procedures are estimated to reduce a woman’s lifetime risk of ovarian cancer by 24% to 34% [5,6]; however, women undergoing salpingectomy have a 64% risk reduction for serous epithelial ovarian and primary peritoneal carcinoma compared with women who have tubal occlusion or no permanent contraception procedure [7]. Furthermore, recent studies have shown no increased surgical risks with salpingectomy compared to occlusive procedures during laparoscopy, except for a minimal increase in operative time [8,9], or during cesarean delivery [10]. Use of salpingectomy for permanent contraception is increasing during laparoscopic sterilization and cesarean delivery [11,12] and ACOG has acknowledged salpingectomy as an effective method of contraception that may provide ovarian cancer risk reduction [13].…”
Section: Introductionmentioning
confidence: 99%
“…The study we published [1] was the research article based on the complete final cohort. The previous paper, published in AJOG [2] was only an abstract, based on partial preliminary data, for the SMFM conference, and for that reason its results differ from those of the complete study.…”
mentioning
confidence: 99%